2018
DOI: 10.1007/s10815-018-1185-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-O blood group and outcomes of in vitro fertilization

Abstract: In a prospective cohort study, we confirmed the lack of a significant association between non-O blood type and clinical outcomes of IVF. Further studies are needed to clarify whether non-O blood group has any prognostic relevance in women undergoing IVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…Awartani et al ( 7 ) compared the clinical parameters of 566 IVF treatment cycles with different ABO blood types and found no significant association between blood type and pregnancy rate. This result agrees with another retrospective study ( 19 ) that evaluated the effect of non-O blood type on clinical pregnancy of 497 women and found no statistically significant association between them. For live birth, two retrospective studies on infertile women undergoing IVF came to different conclusions.…”
Section: Discussionsupporting
confidence: 92%
“…Awartani et al ( 7 ) compared the clinical parameters of 566 IVF treatment cycles with different ABO blood types and found no significant association between blood type and pregnancy rate. This result agrees with another retrospective study ( 19 ) that evaluated the effect of non-O blood type on clinical pregnancy of 497 women and found no statistically significant association between them. For live birth, two retrospective studies on infertile women undergoing IVF came to different conclusions.…”
Section: Discussionsupporting
confidence: 92%
“…The main characteristics of the study population have been described previously ( 7 , 9 ). Briefly, consecutive women <40 years who were scheduled for IVF at our University Center of Reproductive Medicine, Ortona General Hospital, Chieti, Italy from March 2015 to July 2017 were eligible.…”
Section: Methodsmentioning
confidence: 99%
“…The thrombophilia panel that was routinely requested included hereditary thrombophilia such as factor V Leiden, prothrombin G20210A mutation, deficiency of protein C, protein S, or antithrombin, and acquired thrombophilia including lupus anticoagulant, and anti-cardiolipin and anti-beta2 glycoprotein antibodies. Thresholds for positivity are described in our previous reports (7,9). The study was approved by the local institutional review board, and all women signed a written informed consent before study procedures.…”
Section: Study Populationmentioning
confidence: 99%
“…One study has observed the relationship between blood group and IVF-ET pregnancy outcomes and found that blood group B is associated with increased live birth rate [ 7 ]. However, subsequent studies have confirmed that ABO blood group is not related to the IVF pregnancy outcome [ 1 , 8 ]. Some studies have also reported the relationship between the ABO blood group and ovarian reserve, and showed that blood group O is more likely to have diminished ovarian reserve (DOR) [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%